Paraquat and MPTP induce neurodegeneration and alteration in the expression profile of microRNAs: the role of transcription factor Nrf2. (December 2017) - Wang, Qingqing; Ren, Nan; Cai, Zhipeng; Lin, Qingxia; Wang, Zhangjing; Zhang, Qunwei; Wu, Siying; Li, Huangyuan
Abstract Both transcription factors (TFs) and microRNAs (miRNAs) can exert a widespread impact on gene expression. In the present study, we investigated the role of Nrf2 in paraquat-induced intracorporeal neurodegeneration and miRNA expression by exposing Nrf2 wild-type and knockout mice to paraquat (PQ) or 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP). Exposure to 10 mg/kg PQ or 30 mg/kg MPTP caused damage to nerve cells in the substantia nigra (SN) in both Nrf2 (+/+) and Nrf2 (−/−) ICR mice, which included cell morphological changes, detectable apoptosis and a significant reduction in the number of dopaminergic (DA) neurons. When mice were exposed to the same PQ dose of 10 mg/kg, significant fewer tyrosine hydroxylase (TH)-positive DA neurons were observed in the Nrf2 (−/−) mice than that in the Nrf2 (+/+) mice. Both Nrf2 deficiency and PQ or MPTP exposure could alter miRNA expression profile in the SN, suggesting the potential involvement of Nrf2 in the PQ-induced or MPTP-induced miRNA expression alteration. The expression of miR-380-3p was altered by the Nrf2-MPTP interaction effect. miR-380-3p/Sp3-mRNA pathway is likely part of the mechanism of MPTP-induced neurodegeneration. Collectively, our results corroborated the protective role of Nrf2 and also demonstrated the essential interaction of Nrf2 with miRNAs in intracorporal neurodegeneration induced by neurotoxicants. Neurodegeneration: Uncovering protective mechanisms The gene expression regulators Nrf2 and small regulatory RNA molecule miR-380-3p protect nerve cells from damage caused by neurotoxins. Huangyuan Li, at Fujian Medical University, China, and colleagues examined the effects of paraquat andMPTP (1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine), two chemicals known to induce parkinsonism, in mice lacking Nrf2, a key mediator of antioxidant and anti-inflammatory responses. They found that after MPTP or paraquat exposure, the extent of neuronal loss in the substantia nigra was greater in mice lacking Nrf2 than in wild-type controls. Moreover, Nrf2 deficiency prevented an upregulation of miR-380-3p following MPTP exposure. These findings implicate miR-380-3p in the mechanism through which Nrf2 protects the brain from Parkinson's disease-related cell death and opens new avenues of investigation for developing more effective neuroprotective therapies.